Transcendental Paradigm In Pancasila - Arie Purnomosidi (Law Doctoral Program Universitas Muhammadiyah Surakarta, 2019)
ABSTRACT Purpose: This article aims to elucidate how the transcendental paradigm in Pancasila. Methodology: The writing of this article used the doctrinal method by using philosophical and theoretical approaches. Finding: Indonesian law tends to be paradigmatic towards power. This condition caused a materialistic and atheistic way of law. Therefore, it has evoked a crisis in law. Supposedly, Pancasila is a legal basis that is based on the spirit of the nation (volkgeist) of Indonesia. Pancasila is a law that is under the characteristics of people in Indonesia, which are more monodualistic and pluralistic in nature. Therefore, Pancasila contains transcendental values, which are sourced from divine values in religious, ethical, and moral law. The transcendental paradigm in Pancasila can be observed from the opening of the 1945 Constitution, which states that the independence of the Indonesian state is due to the blessing of the Almighty God. The opening of the 1945 Constitution is a substantial agreement among the founders of the nation, which forms the basis of the state-building, and the embodiment of the nation's founders. Importance: It is expected that the transcendental paradigm elucidated in this article can be an alternative solution to overcome the Indonesian legal crisis that can mislead human civilization. Originality/novelty: Orientation of Transcendental paradigms in the principle of Pancasila can be the answer to Indonesia's legal problems that tend to be power-oriented. Keywords: Paradigm, Transcendental Law, Pancasila